EVALUASI METODOLOGIS TERHADAP KRITIK ARTHUR JEFFERY TENTANG SURAT AL-FATIHAH - Yoga Perdana Kusuma; Khairunnas Jamal; Mochammad Novendri (LP2M Universitas PTIQ Jakarta, 2025)
This article critically examines Arthur Jeffery's view on the status of Surah al-Fatihah, as presented in his article